2008
DOI: 10.1128/aac.01501-07
|View full text |Cite
|
Sign up to set email alerts
|

First Report of the Emergence of CTX-M-Type Extended-Spectrum β-Lactamases (ESBLs) as the Predominant ESBL Isolated in a U.S. Health Care System

Abstract: Subsequent to the publication of our article, it was recognized that some details of our PCR and sequencing procedures were not thoroughly described. Page 4016, column 1: Lines 17-30 should read as follows. "Amplicons to be sequenced (high-fidelity PCRs) were prepared using Triple Master Taq polymerase (Eppendorf, Westbury, NY) according to the manufacturer's instructions. The high-fidelity PCRs consisted of a final concentration of 2.5 units of Taq polymerase, 5 l of the template DNA, 200 nM of each primer, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
114
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(126 citation statements)
references
References 0 publications
8
114
1
3
Order By: Relevance
“…A high occurrence of CTX-M-type ESBLs in E. coli has also been reported in recent studies 16,30,34,35 . However, the same was not observed for K. pneumoniae, as prevalence rates of 14.8% and 15.8% were reported in studies conducted in France 16 and Norway 35 , respectively.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A high occurrence of CTX-M-type ESBLs in E. coli has also been reported in recent studies 16,30,34,35 . However, the same was not observed for K. pneumoniae, as prevalence rates of 14.8% and 15.8% were reported in studies conducted in France 16 and Norway 35 , respectively.…”
Section: Discussionmentioning
confidence: 90%
“…The frequency of the bla CTX-M gene was 90.4% (104/115). Other researchers also reported high prevalence rates of 92% 33 , 82% 14 , 72% 34 and 70% 10 . The frequency of the bla TEM was 75% (86/115), which resembles the results of the studies conducted in Sweden and Brazil 10,33 .…”
Section: Discussionmentioning
confidence: 92%
“…Lewis et al found that the most common CTX-M-type ESBL was CTX-M-15 in a U.S. health care system (San Antonio, USA) (16). In their report, CTX-M enzymes increased in prevalence from 25% in 2000 to 70% in 2006 among the collected ESBL-producing isolates.…”
Section: Discussionmentioning
confidence: 90%
“…CTX-M-type β-lactamase is one of the most common ESBLs (15) and was reported to be the predominant ESBL among Enterobacteriaceae isolates (16,17). Lewis et al found that the most common CTX-M-type ESBL was CTX-M-15 in a U.S. health care system (San Antonio, USA) (16).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed a recent report draws attention to the emergence of CTX-M types in a US health care system [22].…”
Section: Usamentioning
confidence: 99%